1999
DOI: 10.1002/(sici)1521-4095(199903)11:4<328::aid-adma328>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

‘Tailor-made’ Polymers for the Removal of Lamellar Twinning: Resolution of α-Amino Acids by Entrainment

Abstract: ponents, as well as outgassing of CO 2 . Approximately 1 mg of vaterite spheroids was produced from 1 mL of supersaturated CaHCO 3 solution.Growth of the vaterite spheroids was followed in situ by optical microscopy and by removing samples at intervals of 2, 4, 6, and 18 h from an octane/SDS/CaHCO 3 microemulsion left partially uncovered at 25 C in a Petri dish. Samples of the uppermost dried powder layer, along with some of the thickening underlying microemulsion phase, were removed and immediately washed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 1 publication
0
35
0
Order By: Relevance
“…This is likely due to adsorption to multiple binding sites (polydentate) in addition to the shielding of the crystal surface by the polymer backbone [58]. Polymeric additives also have been successfully applied to prevent lamellar twinning in the cases of methionine, cysteine and valine [60].…”
Section: Methodsmentioning
confidence: 99%
“…This is likely due to adsorption to multiple binding sites (polydentate) in addition to the shielding of the crystal surface by the polymer backbone [58]. Polymeric additives also have been successfully applied to prevent lamellar twinning in the cases of methionine, cysteine and valine [60].…”
Section: Methodsmentioning
confidence: 99%
“…[131][132][133][134][135][136] They found that the incorporation of a small amount (up to a few percent) of enantiomerically-pure additives in the crystallization of chiral systems inhibits the crystallization of one enantiomer dramatically. In their study, Lahav and Leiserowitz encountered the interesting phenomenon of asymmetric induction on the crystallization of non-chiral photopolymerizable dienes into chiral crystals.…”
Section: Crystallization In the Presence Of Synthetic Polymers -Resolmentioning
confidence: 99%
“…Zbaida and Lahav 133,[137][138] continued their research on chiral resolution by crystallization with "tailor-made" additives and extended it from low molecular-weight additives to polymeric-resolving agents. Zbaida described the resolution by the crystallization of a series of racemic compounds such as glutamic acid, threonine, asparagine monohydrate, and histidine, using soluble chiral polymers.…”
Section: Enantioselective Crystallization By Chiral Soluble Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…16 One enantiomorph can thus operate as template for the crystallization of the other, yet obtaining the racemic conglomerate. Since the crystals of D,Lvaline are actually disordered, 17 they have not undergone spontaneous resolution.…”
mentioning
confidence: 99%